Leibrandt, Sarah; Klein-Collins, Rebecca; Lane, Patrick. "Recognizing Prior Learning in the COVID-19 Era: Helping Displaced Workers and Students One Credit at a Time" (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2020)
This brief is one part of a broad landscape analysis focused on policy and practice issues related to the recognition of prior learning and is published by the Western Interstate Commission for Higher Education (WICHE), with funding from Lumina Foundation and Strada Education Network. The landscape analysis focuses on issues arising in the practice of the recognition of prior learning, policies that encourage or limit its adoption, and key research needs and future directions for the field. To see the full series of briefs, as well as original research completed by the Council for Adult and Experiential Learning on the outcomes of PLA recipients, please visit wiche.edu/recognition-of-learning/.